PENGARUH DOSIS VERMIWASH TERHADAP PERTUMBUHAN TANAMAN PAKCOY (Brassica rapa L.) SEBAGAI SUMBER BELAJAR LKPD BERBASIS 5M KELAS XII MATERI PERTUMBUHAN DAN PERKEMBANGAN - Amalia Ramadhani; Muhfahroyin; Suharno Zen (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2026)
The objectives of this research were 1) to determine the effect of Vermiwash on the growth of Pakcoy (Brassica rapa L.) plants, 2) to determine the Vermiwash dose that had the best effect on the growth of Pakcoy (Brassica rapa L.) plants, and 3) to determine if the research results could be utilizied as a reference for biology learning resouces in the form of Students Worksheets (LKPD). This research was experimental, using a Completely Randomized Design (CRD). Was analyzed using ANOVA. The study consisted of 6 replicates with 5 Vermiwash dose treatments, namely 0 mL,100 mL, 200 mL, 300 mL, and 400 mL. Observed parameters included stem height, number of leaves, and fresh weight of Pakcoy plants. Treatment 4 with 400mL was the best dose for the growth and development of Pakcoy plants. The development of the research results into biology learning resources in the form of 5M-based LKPD received a material expert validation score of 97% and a design expert validation score of 84%, both categorizing them as very valid. The conclusion of this research is that Vermiwash administration affects the growth and development of stem height, number of leaves, and fresh weight of Pakcoy plants, and the LKPD received validation from material experts and design experts.